2013
DOI: 10.3758/s13423-013-0563-4
|View full text |Cite
|
Sign up to set email alerts
|

The eyes grasp, the hands see: Metric category knowledge transfers between vision and touch

Abstract: Categorization of seen objects is often determined by the shapes of objects. However, shape is not exclusive to the visual modality: The haptic system also is expert at identifying shapes. Hence, an important question for understanding shape processing is whether humans store separate modality-dependent shape representations, or whether information is integrated into one multisensory representation. To answer this question, we created a metric space of computer-generated novel objects varying in shape. These o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 19 publications
(23 reference statements)
5
42
0
Order By: Relevance
“…Participants on average needed 10.4 (SD = 5.3) blocks to finish the visual training—this is consistent with the data from Wallraven et al [, not reported] in which participants needed 8.5 blocks (SD = 5.9). Only 3 out of 37 participants were not able to finish within 20 blocks—during the final blocks, however, performance for these participants hovered around 92%, showing that they made only one or two errors during last two blocks (16 objects).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Participants on average needed 10.4 (SD = 5.3) blocks to finish the visual training—this is consistent with the data from Wallraven et al [, not reported] in which participants needed 8.5 blocks (SD = 5.9). Only 3 out of 37 participants were not able to finish within 20 blocks—during the final blocks, however, performance for these participants hovered around 92%, showing that they made only one or two errors during last two blocks (16 objects).…”
Section: Resultssupporting
confidence: 89%
“…Average haptic accuracy was 80.5% (SD = 12.4%) ‐ again, this average performance is consistent with a re‐analysis from data of Wallraven et al [, not reported] in which participants achieved 84.5% (SD = 12.9%). Additionally, accuracy scores were normally distributed ( W = 0.94, P > 0.05).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…This fact is demonstrated by cross-modal transfer of knowledge. If a person is trained to visually categorize a set of objects, this person will often be able to categorize novel objects from the same categories when objects are grasped but not seen (Wallraven et al, 2014;Yildirim & Jacobs, 2013). Because knowledge acquired during visual learning is used during haptic testing, this finding suggests the existence of both visual and haptic representations of objects.…”
Section: Introductionmentioning
confidence: 99%